Treatment of Intertrochanteric Femur Fractures in the Elderly via Bipolar Hip Arthroplasty or Proximal Femoral Nail - Özgür Korkmaz; Yıldıray Genç (Southern Clinics of Istanbul Eurasia, 2018)
INTRODUCTION[|]There is a debate about the treatment of intertrochanteric femur fractures in the geriatric population. A proximal femoral nail (PFN), a sliding hip screw, and bipolar hip arthroplasty (BHA) are the most commonly used treatment modalities. The aim of this study was to compare the blood transfusion rate, duration of surgery, and clinical scores of elderly patients treated with cementless BHA and a PFN.[¤]METHODS[|]A total of 38 patients with intertrochanteric femur fractures treated with cementless BHA or a PFN between 2012–2016 were evaluated. In all, 20 patients had surgical treatment with cementless BHA and 18 had surgical treatment with a PFN. All of the patients were evaluated with the Harris Hip Score (HHS) at the last control visit. Blood transfusion rates and the duration of surgery were recorded and the values of both groups were compared statistically.[¤]RESULTS[|]The mean HHS was 81.4+-10.5 for the BHA group and 83.7+-13 for the PFN group. The mean blood transfusion volume was 1.45+-0.6 units for the BHA group and 0.33+-0.48 units for the group treated with a PFN. The mean duration of surgery for the BHA group was 95+-23.1 minutes. In the PFN group, the mean duration of the surgery was 61.8+-7.3 minutes.[¤]DISCUSSION AND CONCLUSION[|]There was a significant difference in the duration of surgery and the blood transfusion volume. The PFN procedure takes less time than BHA, and the blood transfusion volume is smaller. For these reasons, PFN seems to be a better option than BHA.[¤]